Impact of Youth and Adult Informal Science Educators on Youth Learning at Exhibits. Issue 1 (24th February 2022) - McGuire, L.; Hoffman, A. J.; Mulvey, K. L.; Winterbottom, M.; Balkwill, F.; Burns, K. P.; Chatton, M.; Drews, M.; Eaves, N.; Fields, G. E.; Joy, A.; Law, F.; et al.
Abstract: The impact of educators in informal science learning sites (ISLS) remains understudied from the perspective of youth visitors. Less is known about whether engagement with educators differs based on the age and gender of both visitor and educator. Here, visitors (5–17 years old) to six ISLS in the United States and United Kingdom ( n = 488, female n = 244) were surveyed following an interaction with either a youth (14–18 -years old) or adult educator (19+ years old). For participants who reported lower interest in the exhibit, more educator engagement was related to greater self-reported learning. Younger children and adolescents reported more engagement with an adult educator, whereas engagement in middle childhood did not differ based on educator age. Participants in middle childhood showed a trend toward answering more conceptual knowledge questions correctly following an interaction with a youth educator. Together, these findings emphasize the promise of tailoring educator experiences to visitor demographics.